Struggle against slavery - Balwant Singh (Saharanpur, 1998)
In this book, author narrates the social perceptions of his boyhood and university days, and the hurdles one has to face to break the shackles of wrong and cruel age-old social norms and rituals.
Keywords: Civil Servant